Hybrid harmony search-artificial intelligence models in credit scoring - Goh, Rui Ying (2019)
Credit is a type of advanced lending which poses the risk of having default payments. Thus, credit scoring is important to correctly identify defaulters and non-defaulters. Statistical models are the main approaches but recently, Artificial Intelligence (AI) techniques have been popular due to their ability to account for flexible data patterns. Support Vector Machines (SVM) and Random Forest (RF) are the main focus in this study due to their competitiveness in the literature.